Strategi Komunikasi Pemasaran Melalui Media Online Dalam Meningkatkan Volume Penjualan (Studi Kasus Di Toko Dika Frozen Food Malang) - Kholifatul Khasanah; Nur Hidayati; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine and analyze marketing communication strategies through online media in increasing sales volume at the Dika Frozen Food Store. This research is located at the Dika Frozen Food store, Karangploso Malang. This type of research uses descriptive qualitative. The data used are primary data and secondary data, obtained from interviews and questionnaires filled out directly by respondents who are consumers of the Dika Frozen Food store. The sample used is 30 respondents.The sampling technique used was accidental sampling. The marketing promotion strategy used is by using five promotion mixes, namely advertising, personal selling, sales promotion, public relations and direct marketing. The results of this study indicate that social media has a major effect on increasing sales volume. Keywords: online media, and sales volume